Mobile healthcare management - Nurhanisah Ahmad. (2012)
We live in an age whereby technology has become extremely useful in our day to day lives. Only a decade, we find a contrasting difference in the use of mobile devices. Back then, mobile devices were limited to simply calling and messaging. Now, with the advances in technology we find that these mobile devices are capable of all sorts of functions. One common trend is to use the mobile device to track locations of missing persons. In this final year project, it aims to explore this aspect. Its objective is to track the elderly travelling routines and learn the elderly travelling patterns as the elderly go about leading his/her daily lives. It is able to detect unusual travelling patterns and automatically alert the caregiver. All of the above is to be done using only an Android phone. This project covers the collection of tracking data, processing and analysing the data for travelling patterns and detection of abnormal travel routes.